Guía de práctica clínica para el tratamiento quirúrgico de pacientes con urolitiasis en el Seguro Social del Perú (EsSalud) - Pereyra Velásquez, Wilson (2019)
Introduction. This article summarizes the clinical practice guide (CPG) for the surgical treatment of patients with urolithiasis in the Social Security of Peru (EsSalud). Objective. To provide clinical recommendations based on evidence for the surgical treatment of patients with urolithiasis in EsSalud. Method. A guideline group (GEG) constituted by urologists and methodologists was formed, who formulated the clinical questions that were answered within the present CPG. For each of these questions systematic searches of systematic reviews and primary studies (when considered pertinent) were carried out in PubMed during 2018. The evidence was selected to answer each one of the clinical questions posed, later the certainty was evaluated of the evidence using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. Regular work meetings were scheduled, in which the GEG reviewed the evidence and made recommendations, points of good clinical practice, and flow charts; using the GRADE methodology. The CPG was approved with Resolution No. 66-IETSI-ESSALUD-2018. Results. Six clinical questions on the subject of surgical treatment in urolithiasis were addressed. Based on these questions, 5 recommendations were formulated (2 strong recommendations and 3 conditional recommendations), 21 points of good clinical practice, and 3 management flow charts. Conclusion. This article summarizes the methodology and conclusions based on evidence from the CPG for the surgical treatment of patients with urolithiasis in EsSalud.